FILM SEBAGAI MEDIA KOMUNIKASI SOSIAL : STUDI KASUS FILM BERJUDUL KOMANG (2025) - Arni Ernawati; Dzuha Hening Yanuarsari (LP2M ISBI Bandung, 2026)
This study aims to analyze the film Komang (2025) by Naya Anindita as a social communication medium that reflects the reality of marginalized communities in Indonesia. The film Komang by director Naya Anindita is an adaptation of the true story of the love journey of Raim Laode and his wife, Komang Ade Widiandari. This film raises the theme of love across cultures and religions in Indonesia, with the background of Buton Island and Bali. The research method used is a qualitative approach with Roland Barthes' visual semiotic analysis. The results show that the film Komang contains a strong social message related to structural inequality, power relations, and the position of women in society. This film also builds a space for public discussion and acts as a social advocacy medium. Thus, the film is proven to have the potential as an effective social communication tool in contemporary Indonesian cinematic discourse.